Does Universal SEL Promote Academic Success? Examining Learner Outcomes Under Routine Conditions in First-Grade Classrooms - Susan Crandall Hart; James C. DiPerna; Pui-Wa Lei; Hui Zhao; Tianying Sun; Xinyue Li; Kyle Husmann (SAGE Publishing, 2024)
Although proponents suggest that universal social-emotional learning (SEL) programs promote academic achievement, few studies have directly tested these outcomes under routine conditions in schools. Forty first-grade classrooms participated in an effectiveness trial in which schools (N = 13) were randomly assigned to implementation of a universal SEL program (SSIS SEL CIP) or control (business-as-usual practices) conditions within sites/regions. Teachers in the treatment condition prepared for and implemented the program in accordance with their typical local practices. There were no statistically significant main effects on teacher-rated student engagement, motivation, and academic skills. Effect sizes, however, were medium to large and positive for academic engaged time and math achievement. Students with lower teacher-rated academic motivation at pretest also were more likely to improve after program exposure. These findings help identify considerations for further studying the potential academic outcomes resulting from implementing universal SEL under typical conditions.